Networks as a key factor for the consolidation of new worker cooperatives - Cuñat Giménez, Rubén J. (REVESCO. Revista de Estudios Cooperativos, 2015)
In the last years of crisis and job losses, interest in boosting the dynamism and growth of the economy in a geographic area through the creation of new firms has been increasing. Worker cooperatives (CTA) represent a business model in which the economic objectives are combined with social, achieving growth based on employment, social equality and equity. New CTA need knowledge to its consolidation, one part of which comes from the training and experience of its promoters, and another of the interpersonal and interorganizational relationship within its economic and social environment. The survival and growth of the CTA will be very influenced by their ability to maintain and extend their networks. This paper aim to contribute to the knowledge of the different types of networks that is related to a cooperative from birth to consolidation, as well as the impact on their survival and growth. We have made a total of 36 in-depth interviews using a qualitative methodology (Grounded Theory) with promoters of CTA created in the period 2006-2007, all of them located in the Valencian Community.
Keywords: Entrepreneurship; Worker cooperatives; Grounded theory; Network; Viability.